Infection Control Attitude, Knowledge and Awareness Level Among Dental Students and Interns in the Removable Prosthodontic Department at the Faculty of Dentistry, University of Benghazi, Libya - H E Elgtlawi, Mohamed; M Lefsaay, Amel; O Elaogali, Omar; M Bushaala, Fatma; Hamad, Mardia (Libyan Journal of Dentistry, 2024)
Background: Dental students have increased patient contact during their education and clinical practice, putting them, their patient population and Dental Health Care Workers (DHCW) at high risk of cross-infection. Awareness of infection control principles may help in preventing disease transmission; therefore, the purpose of this study was to evaluate the level of infection control knowledge, attitude, and practice among dental students and interns in a removable prosthodontic department at the Faculty of Dentistry, University of Benghazi, Libya. Materials and Methods: In May 2023, we distributed questionnaires containing 33 items to interns, 3rd-year, and 4th-year dental students at the faculty. The questions covered topics such as hepatitis B vaccination, use of personal protective barriers, knowledge of infection control protocols, and practice in the removable prosthodontic department of the faculty. Descriptive statistics were recorded using frequency and percentages. Differences in proportions were assessed using the Chi-square and Fisher exact test. All statistical analyses were performed at a p-value less than 0.05. Results: A total of four hundred and ten (410) participants responded to the questionnaire. Around 21.5% of the students had completed their hepatitis B vaccination, while 41.2% had never been vaccinated. Regarding the self-reported use of protective barriers, intern students showed a significantly higher score than did other study groups (P <0.001). Moreover, the vast majority of 3rd year students reported never wearing eyewear, a face shield, or the head cap (73.2%), (81.1%), or (70.1%), respectively. About two-thirds of intern students (69.4%) showed positive attitudes toward the treatment of patients with infectious diseases. Conclusion: This study showed moderate compliance to infection control procedures among the participants, they have limited orientation and knowledge of the infection control guidelines and policies. Despite a positive attitude toward infection control measures, proper infection control practices were not consistently followed. Consequently, it is essential to take action to ensure that students understand the critical importance of practicing cross-infection control. Higher education institutions should implement effective solutions to address this issue.